γδ T cell-mediated activation of cDC1 orchestrates CD4+ Th1 cell priming in malaria - Ibraheem, Yarob; Bayarsaikhan, Ganchimeg; Macalinao, Maria Lourdes; Kimura, Kazumi; Yui, Katsuyuki; Aoshi, Taiki; Inoue, Shin-Ichi (Frontiers in Immunology, 2024)
γδ T cells facilitate the CD4 + T helper 1 (Th1) cell response against Plasmodium infection by activating conventional dendritic cells (cDCs), although the underlying mechanism remains elusive. Our study revealed that γδ T cells promote the complete maturation and production of interleukin-12 and CXCR3-ligands specifically in type 1 cDCs (cDC1), with minimal impact on cDC2 and monocyte derived DCs (Mo-DCs). During the initial infection phase, γδ T cell activation and temporal accumulation in splenic white pulp, alongside cDC1, occur via CCR7signaling. Furthermore, cDC1/γδ T cell interactions in the white pulp are amplified through CXCR3 signaling in γδ T cells, optimizing Th1 cell priming by cDC1. We also demonstrated how transitional Th1 cells arise in the white pulp before establishing their presence in the red pulp as fully differentiated Th1 cells. Additionally, we elucidate the reciprocal activation between γδ T cells and cDC1s. These findings suggest that Th1 cell priming is orchestrated by this reciprocal activation in splenic white pulp during the early phase of blood-stage Plasmodium infection.